2015
DOI: 10.1038/nm.3952
|View full text |Cite|
|
Sign up to set email alerts
|

Combined inhibition of BET family proteins and histone deacetylases as a potential epigenetics-based therapy for pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal human cancers and shows resistance to any therapeutic strategy used. Here we tested small-molecule inhibitors targeting chromatin regulators as possible therapeutic agents in PDAC. We show that JQ1, an inhibitor of the bromodomain and extraterminal (BET) family of proteins, suppresses PDAC development in mice by inhibiting both MYC activity and inflammatory signals. The histone deacetylase (HDAC) inhibitor SAHA synergizes with JQ1 to augment cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
322
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(349 citation statements)
references
References 81 publications
23
322
2
2
Order By: Relevance
“…These findings are consistent with the previous reports that show that JQ1 inhibits inflammation in pancreatic ductal adenocarcinoma [40] and a murine periodontitis model [41]. Thus, our study implicates that JQ1 might also reduce inflammation in NSCLC cells.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with the previous reports that show that JQ1 inhibits inflammation in pancreatic ductal adenocarcinoma [40] and a murine periodontitis model [41]. Thus, our study implicates that JQ1 might also reduce inflammation in NSCLC cells.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to the human PdX models, JQ1 activity was recently demonstrated in a genetically engineered PDAC mouse model (GEMM). Here, MYC and proinflammatory pathways were blocked by JQ1 (12). In sum, preclinical data argue that BET-I-based therapies should be further developed.…”
Section: Targeting Myc Indirectlymentioning
confidence: 86%
“…MYC alone is sufficient to initiate tumors and to drive tumor progression in the pancreas in vivo (5,(7)(8)(9)(10). Furthermore, compelling evidence exists that MYC is an essential downstream effector of oncogenic KRAS in the pancreas (11)(12)(13)(14). MYC expression is controlled at several layers in PDAC (15).…”
mentioning
confidence: 99%
“…Mechanistically, combined inhibition of AURKA mitotic kinase and H3K9 HMTs triggers uncoordinated checkpoint responses in G2/M, disrupting the cell cycle and leading to mitotic catastrophe. Dr. Jens Siveke presented recent work highlighting the importance of patient stratification in treating pancreatic cancer, as 30% of PDAC patients have alterations in epigenomic regulators [30]. His group showed synergism between the histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) and JQ, an inhibitor of bromodomain and extraterminal (BET) proteins, in suppressing PDAC, but only in a subset of tumor xenografts.…”
Section: Translational Value Of Epigenetics For Gi Disease Diagnosismentioning
confidence: 99%
“…However, transcriptome studies of PDAC samples have suggested the division of this disease into classical, quasimesenchymal, and exocrine-like subtypes on the basis of differential gene expression and histological differences within subtypes [34]. As mentioned above, Dr. Jens Siveke identified different PDAC subtypes based on differential sensitivity to drugs such as HDAC and BET inhibitors [30]. Higher levels of the lncRNA CCAT1 correlated with increased sensitivity to HDAC inhibitors, which is already used to predict sensitivity to BET inhibitors in colorectal cancers.…”
Section: Translational Value Of Epigenetics For Gi Disease Diagnosismentioning
confidence: 99%